Bridging Service and Digital Experience: Understanding Customer Satisfaction in Intercity Bus Transport - Syahru Utama, Afwan; Arif, Moh. Erfan (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose – This study aims to examine the effects of perceived service quality and e-service quality on customer satisfaction among users of 27 Trans' intercity and interprovince bus transportation services.   Design/methodology/approach – This study employs a quantitative explanatory research design to examine the relationships among the proposed variables through hypothesis testing. Using a purposive sampling technique, data were collected from 120 respondents aged at least 18 years who had used 27 Trans services and purchased tickets through the 27 Trans online ticketing application. The data were gathered using Likert-scale questionnaires and analyzed using multiple linear regression in IBM SPSS Statistics 26.   Findings – The results demonstrate that both perceived service quality and e-service quality have a positive and significant effect on customer satisfaction. These findings highlight the importance of delivering high-quality transportation services alongside efficient digital ticketing services to improve customer satisfaction.   Originality/value – This study contributes to the understanding of how traditional transportation services can integrate digital service quality with perceived service excellence to strengthen customer satisfaction in the era of business digitalization, particularly within Indonesia’s intercity and interprovince bus industry.